Golf ball - Brown, Harry J. (Harry John), 1972- (New York : Bloomsbury Academic, 2015)
Object Lessons is a series of short, beautifully designed books about the hidden lives of ordinary things. Harry Brown explores the composition, history, kinetic life, and the long deterioration of golf balls, which as it turns out may outlive their hitters by a thousand years, in places far beyond our reach. Golf balls embody our efforts to impose our will on the land, whether the local golf course or the Moon, but their unpredictable spin, bounce, and roll often defy our control. Despite their considerable technical refinements, golf balls reveal the futility of control. They inevita.
10 How the Golf Ball Vanishes Before YourÂ Eyes11 How the Golf Ball Makes Us FeelÂ Fulfilled, forÂ a Millisecond; 12 How to Control the Unruly Golf Ball; 13 How to Hit the Golf Ball by Not Hitting It; 14 How the Golf Ball Looks into the Abyss, and the Abyss Looks Back; 15 How the Golf Ball Won the Golden Fleece; 16 How the Golf Ball Went to theÂ Moon; 17 How the Golf Ball Makes Friends with Animals; 18 How the Golf Ball Prepares for Doomsday; Notes; Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Golf balls -- History; Balles de golf -- Histoire; Media studies; Philosophy: aesthetics; Cultural studies; Literary theory; GAMES -- Gambling -- Sports; SPORTS & RECREATION -- Business Aspects; SPORTS & RECREATION -- Essays; SPORTS & RECREATION -- History; SPORTS & RECREATION -- Reference; TRAVEL -- Special Interest -- Sports; Golf balls; History